MODEL KETAHANAN MASYARAKAT LERENG MERAPI TERHADAP ERUPSI DI KABUPATEN SLEMAN YOGYAKARTA - , Ikhwanuddin ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mount Merapi, with specific type in its eruption 2 â 5 years for short eruption and 5 â 7 years for long eruption. Its characteristics cause level of disaster risk intensity in the surrounding areas become high, the risk level become because many people remain to stay deliberately in the surounding region. The series of events of mount Merapi eruptions, do not necessarily make people to move or find a safer place to live. In contrast, population growth around Merapi mountain or in disaster-prone areas, end to increase or not appropriately controlled. This study aims to describe the efforts of the community to face the disaster. Further, itâs to formulate a descriptive model of community who live in the slope area of mount Merapi in facing eruption or other related disaster, descriptive model of community resilience will later be used as a base to develop an alternative model of resilience for the community. It means that the study does not explore an ideal model based on community characteristics. The preparation of the model is initiated by analyzing all primary data and linking the secondary data, the analysis of data was conducted based on specific data from the field into units of information. The next step, description of the data performs a significant inventory of statement relevant to the topic, and in detail then grouped into several related themes. After categorization then understanding of meaning of the case is done by connecting among interview results, behavior, and other aspects. Finally these qualitative information is processed and other aspects inductively. Based on the analysis, the study formulated that the supporting elements to build community resilience can be viewed bran level of public awareness, form of community economic strategy in the community function of local wisdom adapted in the lives of local communities, and land use management. Furthermore, bran these elements, the study obtained that the concept of community resilience to the Merapi mountain slope area is influenced by the general community ability to build resiliency, functions of government or non-government agencies, as well as physical support of the area